Gerra hemen hasten da = La guerra empieza aquí (Ongi Etorri Errefuxiatuak, 2019)
The action of a firefighter in the Port of Bilbao, by refusing to participate in a shipment of weapons to massacre the population of Yemen, initiates a social movement that will unveil the dark interests and implications of this trade. --